Bioinformatic Analysis of Drug Candidate Compounds for Acquired Immunodeficiency Syndrome - Sukoco, Restu Megadiana; Fauzi, Ahmad; Nuha, Ulin (Proceeding International Conference on Global Resource Conservation, 2015)
AIDS is a syndrome caused by HIV. The immune system of AIDS patient was too weak to fight off many infections. Many drugs developed to overcome these deadly disease. In this study, bioinformatic analysis performed on some drug candidate compounds that under development of FDA for AIDSâ patient. The drug candidate compounds are Amdoxovir, Alovudine, Elvucitabine, Dexelvucitabine, Capravirine, Darunavie, Calanolide-A, Tipranavir and Enfuvirtide. Molinspiration and preADMET web server has been used as tool for analyzing that drugs. As a results, our study revealed that not all of these drug candidate compounds fulfilled the Lipinskiâs rule of five and toxicity test standart in silico.Keywords:Bioinformatic analysis; AIDSâ drug; Lipinskiâs rule; toxicity test